A voice of their own : the authority of the local parish - Clark, William A. (William Anthony), 1958- (Collegeville, Minn. : Liturgical Press, 2005)
"Examines 'community,' intimacy,' and 'authority' in the church at the formative, local ecclesial level; examines contributions of several theologians; concludes that a deeper appreciation for the enormous, practical authority of local communities can help ground a renewal of the church's self-understanding"--Provided by publisher.
Church and the local community -- Church, in three places -- The problem of community -- Intimacy, authenticity, and the foundations of community -- Authority : authentic Christian life speaks to the church -- Local authority and the "priority of the universal" -- Local community and the church's mission : the work of Karl Rahner -- Local community and the exercise of authority : a summary and a look ahead.
"A Michael Glazier book."
Includes bibliographical references (p. 201-210) and index.
Keywords: Fellowship -- Religious aspects -- Christianity; Communities -- Religious aspects -- Christianity; Church -- Authority; Authority -- Religious aspects -- Christianity; Church